2020
DOI: 10.1183/13993003.01192-2019
|View full text |Cite
|
Sign up to set email alerts
|

CILP1 as a biomarker for right ventricular maladaptation in pulmonary hypertension

Abstract: The aim of our study was to analyse the protein expression of cartilage intermediate layer protein 1 (CILP1) in a mouse model of right ventricular (RV) pressure overload and to evaluate CILP1 as a biomarker of cardiac remodelling and maladaptive RV function in patients with pulmonary hypertension (PH).Pulmonary artery banding was performed in 14 mice; another 9 mice underwent sham surgery. CILP1 protein expression was analysed in all hearts by western blotting and immunostaining. CILP1 serum concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 34 publications
(11 reference statements)
5
30
1
Order By: Relevance
“…Keranov et al . 14 reported that serum CILP‐1 levels are significantly higher in patients with HF than in healthy controls, which is in line with our results showing that serum CILP‐1 levels are positively correlated with NT‐proBNP. However, Park et al .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Keranov et al . 14 reported that serum CILP‐1 levels are significantly higher in patients with HF than in healthy controls, which is in line with our results showing that serum CILP‐1 levels are positively correlated with NT‐proBNP. However, Park et al .…”
Section: Discussionsupporting
confidence: 92%
“…Transforming growth factor‐β1 plays an important role in the pathogenesis of cardiac remodelling by activating pro‐fibrotic signalling pathways that promote ECM synthesis and myofibroblast transdifferentiation. 18 As an antagonist of TGF‐β1 signalling, cardiac CILP‐1 can be rapidly induced by TGF‐β1, 7 , 10 , 14 thus creating a negative feedback loop. However, opposing observations regarding the circulating CILP‐1 expression have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, cartilage intermediate layer protein 1 (CILP1), an extracellular matrix (ECM) protein involved in profibrotic signaling in the myocardium [ 138 ], was recently described as a novel biomarker of RV and LV pathological remodeling in patients with pulmonary hypertension. In one study, maladaptive RV patients had higher CILP1 concentrations than controls and those with LV hypertrophy and dilated cardiac myopathy in [ 139 ]. Previously, expression at the RNA level in heart mouse models was shown to be more pronounced in RV pressure overload than in LV pressure overload [ 140 ].…”
Section: A Clinical and Experimental Therapeutic Approach To Rv Dysfunctionmentioning
confidence: 99%